Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1167/iovs.62.15.10
|View full text |Cite
|
Sign up to set email alerts
|

Aged Nrf2-Null Mice Develop All Major Types of Age-Related Cataracts

Abstract: Purpose Age-related cataracts affect the majority of older adults and are a leading cause of blindness worldwide. Treatments that delay cataract onset or severity have the potential to delay cataract surgery, but require relevant animal models that recapitulate the major types of cataracts for their development. Unfortunately, few such models are available. Here, we report the lens phenotypes of aged mice lacking the critical antioxidant transcription factor Nfe2l2 (desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Interestingly, Pxdn has recently been recognized to be a target of the TF Nrf2 (Hanmer and Mavri-Damelin, 2018), which is an established partner protein of small Mafs, binding together of which impact their downstream control over target genes (Katsuoka et al, 2005). Further, Nrf2 deficiency is associated with lens defects and cataract (Rowan et al, 2021). Thus, overexpression of Pxdn, resulting from Mafg, Mafk deletion, may impact cell proliferation and altered ECM, which together contribute to the epithelial defects observed in Mafg −/− :Mafk −/− lens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pxdn has recently been recognized to be a target of the TF Nrf2 (Hanmer and Mavri-Damelin, 2018), which is an established partner protein of small Mafs, binding together of which impact their downstream control over target genes (Katsuoka et al, 2005). Further, Nrf2 deficiency is associated with lens defects and cataract (Rowan et al, 2021). Thus, overexpression of Pxdn, resulting from Mafg, Mafk deletion, may impact cell proliferation and altered ECM, which together contribute to the epithelial defects observed in Mafg −/− :Mafk −/− lens.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that mice with homozygous deletion of the gene encoding nuclear factor erythroid 2–related factor 2 (Nrf2, also known as Nfe2l2) develop significant cataracts late in life (11–15 months of age) at a higher frequency than wild-type mice of comparable ages ( Rowan et al, 2021 ). Although the mechanism responsible for development of these cataracts has not been determined, it is possible that these mice have less protection against oxidative stress and therefore age faster.…”
Section: In Some Cataract Models Changes Of Fiber Cell Connexins and ...mentioning
confidence: 99%
“…In physiological conditions, Keap1 can increase the nuclear factor and erythroid 2-related factor 2 (Nrf2) proteasomal degradation. Since Nrf2 controls the basal and induced expression of a number of antioxidant-response genes, it is evident that the reduction of Keap1-induced ROS increases the degradation of Nrf2 and, as a result, reduces a cell’s antioxidant control system [ 53 , 54 , 55 ]. The consequence is that oxidative damage increases exponentially, along with the development of cataracts of the lens.…”
Section: Reactive Oxygen Species and Eye Healthmentioning
confidence: 99%